2020
DOI: 10.1186/s13223-020-00462-w
|View full text |Cite
|
Sign up to set email alerts
|

The clinical, immunological and genetic features of 12 Chinese patients with STAT3 mutations

Abstract: Background Loss-of-function (LOF) mutations in signal transducer and activator of transcription 3 (STAT3) is one of the causes of STAT3 hyperimmunoglobulin E (IgE) syndrome (STAT3-HIES), while gain-of-function (GOF) mutations in STAT3 lead to immune dysregulation diseases. We retrospectively analyzed the age, common clinical symptoms, immunologic and molecular manifestations in 11 patients with LOF STAT3 mutations and 1 patient with a GOF STAT3 mutation. Methods Twelve patients were enrolled in our study. Se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Despite having mutations in different domains of STAT3, all patients showed similar kinds of defective B cell function ex-vivo results. It was reported that these mutations were all LOF STAT3 mutations and led to impaired STAT3 signaling (34,35), which might have a similar effect on patients' B cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Despite having mutations in different domains of STAT3, all patients showed similar kinds of defective B cell function ex-vivo results. It was reported that these mutations were all LOF STAT3 mutations and led to impaired STAT3 signaling (34,35), which might have a similar effect on patients' B cell function.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical phenotype of patients with AR ZNF341 deficiency is essentially a phenocopy of AD STAT3 deficiency. However, it has milder consequences, as illustrated by the median HIES NIH (National Institutes of Health) score of 28.5 for these patients, as opposed to 64 for patients with AD STAT3 deficiency ( Table 1 ) [ 18 , 19 , 25 33 ]. Atopic dermatitis was the most common clinical presentation of patients with ZNF341 deficiency, present in all patients reported, a proportion similar to that for patients with STAT3 deficiency (> 90%).…”
Section: Introductionmentioning
confidence: 99%